PRODUCTION OF PROTEIN HYDROLYSATES FROM FISH SKIN FOR DAIRY PRODUCTS (Proceedings of International Conference on BioScience and Biotechnology, 2019)
The aim of this research was studying the fish protein hydrolysates (FPH) produced from Salmon (Salmo salar) skin prepared by different methods. Four methods were used: enzymatic hydrolysis, acid hydrolysis, chemical (with acids or alkalis) and enzymatic hydrolysis with preserving agents upon the heating proposed to produce fish protein hydrolysates (FPH). All methods modified and adapted to optimized researches. All hydrolysates were vacuum freeze-dried and collagen content was determined in them. Depending on the collagen content in the FPH, methods may be ranked as follows: chemical method (with acids or alkali) (15,1%) < enzymatic hydrolysis (26,5%) < acid hydrolysis (30,0%) < enzymatic hydrolysis with preserving agents upon the heating (37,5%). The results showed that FPH prepared using enzymatic hydrolysis with preserving agents upon the heating had a greater amount of protein than FPH prepared using other methods. Citric acid preparation and sesame seeds covered the initial fish odour and off-flavours generated in fish hydrolysates. The sensory analysis of the final product allowed choosing the most rational content of components. Hydrolysis with preserving agents on the heating allowed obtaining collagen hydrolysate in dry form and without fish smell. This FPH may be used as a stabilizer in dairy products.
Keywords: fish protein hydrolysates; hydrolysis; fish odour; dairy products